Evaluasi Implementasi Kurikulum Merdeka: Tantangan dan Peluang - Situmorang, Lidia Kristiani; Ayuningsih, Pitri; Hilaliyah, Tatu (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to evaluate the implementation of the Independent Curriculum at SMAN 6 Kota Serang, focusing on the challenges and opportunities faced in its implementation. The approach used is qualitative with a case study method, involving in-depth interviews with the Vice Principal for Curriculum. The results of the study indicate that: First, the implementation of the Independent Curriculum faces major challenges, namely teacher adjustment and the application of technology in learning. Teachers need to adjust to changes in the curriculum that are more flexible and technology-based, while schools face the need to strengthen facilities and training. Second, the implementation of technology such as the use of Google Form, Google Meet, and Google Classroom has increased the interactivity of learning, although there are technical obstacles that must be overcome. Third, full support from the school in the form of training, facilities, and collaboration between teachers has proven to be important for the success of the implementation of the Independent Curriculum